“We are not blind researchers” - Lindokuhle Deyi Ubisi; Patrone Rebecca Risenga; Wandile Fundo Tsabedze; Thandazile Mathabela; Keatlegile Moses Eskia Mabena; Mafikeni Andries Mnguni; Nonhlanhla Masinga; Bantubenzani Nelson Mdlolo; Ncumisa Genqese; Matimu Nkuna; Alice Mathebula; Evelyn Morake; et al. (The Thinker)
Our community engagement project aimed to capacitate secondary school teachers of visually impaired learners to use anatomically correct models during their comprehensive sexuality education lessons. Given that the beneficiaries of this project were ultimately visually impaired learners, as sighted researchers, we approached entry into schools for the blind with the need to acknowledge our privilege as able-bodied researchers. With the principle of “nothing about us, without us”, we further relied on two blind professors both locally and internationally as experts to guide our community praxis (i.e., how to position ourselves and manage possible resistance due to being outsiders). However, upon entering this space, we not only found that most staff (e.g., teachers) working with visually impaired learners were sighted. More importantly, our engagement within this space led us to realize that preoccupation with privilege tended to essentialize the powerlessness of people with disabilities (PwDs) more broadly. Moving from the decolonial project, we found that seeing ourselves as ‘privileged’ reproduced a charity model where PwDs are viewed as objects of pity, reliant on their able-bodied counterparts to be included in society. We found that the acknowledgement of power was a catharsis for us with limited benefit methodologically but with its own caveats.